Factors Influencing the Adoption of Vegetable Farmers to Organic Agriculture System in Batur Village Getasan District Semarang Regency - Toni Wijaya; Tinjung Mary Prihtanti (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Using chemical fertilizers and pesticides in conventional agriculture harms the environment and consumer health. Therefore, it is necessary to develop organic farming to create sustainable agriculture. This research analyses the factors influencing vegetable farmers' adoption of the organic farming system in Batur Village, Getasan District, Semarang Regency. The method used in this research is a quantitative approach. The data collection technique uses interview techniques with questionnaire tools. The sample was determined using a saturated sample with 67 respondents. The analysis used is binary logistic regression. This research concludes that the variables education, experience, and characteristic innovation significantly increase the probability of vegetable farmers adopting the organic farming system. Meanwhile, age, land area, and access information do not significantly affect organic farming systems adoption.